2004
DOI: 10.1093/humrep/deh279
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of human multipotent mesenchymal stem cells from second-trimester amniotic fluid using a novel two-stage culture protocol

Abstract: We demonstrate that human multipotent MSCs are present in second-trimester amniotic fluid. Considering the great potential of cellular therapy using fetal stem cells and the feasibility of intrauterine fetal tissue engineering, amniotic fluid may provide an excellent alternative source for investigation of human MSCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
446
3
36

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 595 publications
(507 citation statements)
references
References 25 publications
16
446
3
36
Order By: Relevance
“…After these treatments, AFCs gave rise to adipocytes and osteoblasts, when fibroblasts were the predominant cell population. In this regard, it has been reported [10,12,13] that amniotic fluid mesenchymal stem cells display a multilineage differentiation potential into fibroblasts, adipocytes and osteocytes. We suggest that the limited differentiation potential towards mesenchymal lineages that we found in our AFC cultures could be due to the cell heterogeneity with high percentage of epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After these treatments, AFCs gave rise to adipocytes and osteoblasts, when fibroblasts were the predominant cell population. In this regard, it has been reported [10,12,13] that amniotic fluid mesenchymal stem cells display a multilineage differentiation potential into fibroblasts, adipocytes and osteocytes. We suggest that the limited differentiation potential towards mesenchymal lineages that we found in our AFC cultures could be due to the cell heterogeneity with high percentage of epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Amniotic epithelial cells obtained from cesarean sections have been shown to express markers for neuronal, glial and progenitor cells and to differentiate into neuron-like cells in the ischemic brain of adult rats [7][8][9]. Moreover, there is evidence that amniotic fluid contains fetal mesenchymal stem cells with a multilineage differentiation potential [10][11][12][13]. In this study we extensively characterized unselected amniotic cells and tested their multilineage differentiation capacity in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies have demonstrated the ability to isolate amniotic membrane stem cells (AMSCs) and amniotic fluid stem cells (AFSCs) (In 't Anker et al 2003;Tsai et al 2004;Tsai et al 2006). These cells have phenotypes attributable to pluripotent cells and can differentiate into different cell types due to the three different embryonic layers (De Coppi et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the deliberately simple and easily reproducible methodology for isolation of amniotic and placental MSCs described here and in our previous work, other methods that rely on oxygen tension, two-stage cultures, or alternative media formulations have been reported [11,12]. It remains to be seen whether these alternatives would lead to any advantage, or disadvantage, in clinical-grade processing.…”
Section: Discussionmentioning
confidence: 96%